Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1089/ast.2014.1143
|View full text |Cite
|
Sign up to set email alerts
|

Astrobiological Stoichiometry

Abstract: Chemical composition affects virtually all aspects of astrobiology, from stellar astrophysics to molecular biology. We present a synopsis of the research results presented at the ''Stellar Stoichiometry'' Workshop Without Walls hosted at Arizona State University April 11-12, 2013, under the auspices of the NASA Astrobiology Institute. The results focus on the measurement of chemical abundances and the effects of composition on processes from stellar to planetary scales. Of particular interest were the scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 163 publications
(167 reference statements)
0
23
0
Order By: Relevance
“…If the trace element stoichiometry of life on Earth is but a sort of chemical ‘vestigial characteristic’ of the environment in which it emerged, one might expect lifeforms in extraterrestrial environments to use trace metals for redox metabolism in proportions that also mirror the environment of their emergence. Some extrasolar environments seem to provide an elemental supply radically different from Earth's (Young et al ., ); thus, we do not expect the trace elemental ranges reported in this study to hold for putative life that may have emerged in such exotic planetary settings.…”
Section: Discussionmentioning
confidence: 72%
“…If the trace element stoichiometry of life on Earth is but a sort of chemical ‘vestigial characteristic’ of the environment in which it emerged, one might expect lifeforms in extraterrestrial environments to use trace metals for redox metabolism in proportions that also mirror the environment of their emergence. Some extrasolar environments seem to provide an elemental supply radically different from Earth's (Young et al ., ); thus, we do not expect the trace elemental ranges reported in this study to hold for putative life that may have emerged in such exotic planetary settings.…”
Section: Discussionmentioning
confidence: 72%
“…Though typically constituting only ∼1.5% of a star's mass, the elements with Z > 2 play an essential role in the origins and evolution of terrestrial planets. Young et al (2014) summarized the findings of several observational astronomy groups engaged in quantitative spectroscopic measurements of stars to determine element abundances and ratios-an effort known as "stellar stoichiometry." They concluded that stellar concentrations and relative amounts of such key elements as Al, C, Ca, Mg, Na, O, and Si may differ by factors of at least two compared to the Sun.…”
Section: Stellar Stoichiometrymentioning
confidence: 99%
“…McKinnon et al (2008) cautioned that any direct extrapolation from present-day comets to volatiles accreted by KBOs overlooks evolutionary effects on cometary volatile-to-water ratios (e.g., Shock and McKinnon, 1993). Interstellar cloud abundances and direct observation of inner extrasolar disk compositions are also biased, because the bulk compositions of extrasolar systems may be widely different from that of the solar system (Young et al, 2014 (Mumma and Charnley, 2011) that are of same order of magnitude as those observed in extrasolar disks (Maret et al, 2006;Carr and Najita, 2008), although the CO 2 abundances differ significantly. The general consistency between these values provides guidance to estimate primordial volatile abundances in the solar system.…”
Section: Volatile Inventory Of Kbosmentioning
confidence: 99%